The effect of sucrase-isomaltase deficiency on metabolism, food intake and preferences: protocol for a dietary intervention study. Issue 1 (31st December 2023) - Senftleber, Ninna Karsbæk; Skøtt Pedersen, Kristine; Schnoor Jørgensen, Cecilie; Pedersen, Hanne; Bjerg Christensen, Marie Mathilde; Kabel Madsen, Emilie; Andersen, Kristine; Jørsboe, Emil; Gillum, Matthew Paul; Frøst, Michael Bom; Hansen, Torben; Jørgensen, Marit Eika
ABSTRACT: In Greenland, traditional marine foods are increasingly being replaced by sucrose- and starch-rich foods. A knock-out c.273_274delAG variant in the sucrase-isomaltase ( SI ) gene is relatively common in Greenland, with homozygous carriers being unable to digest sucrose and some starch. The variant is associated with a healthier metabolic phenotype in Greenlanders, which is confirmed by SI -knockout mice. We aim to assess if the healthy phenotype is explained by metabolic and microbial differences and if food and taste preferences differ between SI -genotypes. This paper describes the protocol for a randomised cross-over trial conducted in Greenland in 2022 with two dietary interventions of three days; a traditional meat- and fish-rich diet and a starch-rich Western diet with 11 energy% sucrose. The power calculation showed that 22 homozygous SI -carriers and 22 non-carriers were sufficient to detect a 0.5 mmol/L difference in glycaemic variability (80% power, α=0.05). We enrolled 18 carriers and 20 non-carriers. We examined food preferences at baseline and collected samples before and after each intervention for metabolic, metabolome, and microbiome profiling. Analyses of samples have not been completed yet. The Ethics Committee of Greenland approved the study. Results will be disseminated in international peer-reviewed journals and to the general Greenlandic population. NCT05375656.